Retrieval of Suspended Particulate Matter in Inland Waters with Widely Differing Optical Properties Using a Semi-Analytical Scheme - Bernardo, Nariane [UNESP]; Carmo, Alisson do [UNESP]; Park, Edward; Alcantara, Enner [UNESP] (Mdpi, 2019)
Suspended particulate matter (SPM) directly affects the underwater light field and, as a consequence, changes the water clarity and can reduce the primary production. Remote sensing-based bio-optical modeling can provide efficient monitoring of the spatiotemporal dynamics of SPM in inland waters. In this paper, we present a novel and robust bio-optical model to retrieve SPM concentrations for inland waters with widely differing optical properties (the Tiete River Cascade System (TRCS) in Brazil). In this system, high levels of Chl-a concentration of up to 700 mg/m(3), turbidity up to 80 NTU and high CDOM absorption highly complicate the optical characteristics of the surface water, imposing an additional challenge in retrieving SPM concentration. Since K-d is not susceptible to the saturation issue encountered when using remote sensing reflectance (R-rs), we estimate SPM concentrations via K-d. K-d was derived analytically from inherent optical properties (IOPs) retrieved through a re-parameterized quasi-analytical algorithm (QAA) that yields relevant accuracy. Our model improved the estimates of the IOPs by up to 30% when compared to other existing QAAs. Our developed bio-optical model using K-d(655) was capable of describing 74% of SPM variations in the TRCS, with average error consistently lower than 30%.
Keywords: semi-analytical model; inherent optical properties; light attenuation; water quality monitoring